1984
DOI: 10.1901/jaba.1984.17-313
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Immunization of Preschool Children; An Evaluation of Applied Community Interventions

Abstract: We evaluated the relative impact of four procedures designed to encourage parents to obtain immunizations for their children. In a public health setting, the families of 1,133 immunizationdeficient preschool children were randomly assigned to six conditions: (a) a general prompt; (b) a more client-specific prompt; (c) a specific prompt and increased public health clinic access; (d) a specific prompt and monetary incentives; (e) contact control; and (f) no contact control. All interventions, except the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 20 publications
1
46
1
Order By: Relevance
“…Four studies were identified that met the criteria for inclusion in the effectiveness component, [23][24][25][26] 6 studies for inclusion in the acceptability component, [27][28][29][30][31][32] and 1 for inclusion in the economic component (Fig 1). 31 Studies included in the effectiveness component consisted of 1 cluster randomized controlled trial (RCT), 26 2 nonclustered RCTs, 23,24 and 1 time series analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies were identified that met the criteria for inclusion in the effectiveness component, [23][24][25][26] 6 studies for inclusion in the acceptability component, [27][28][29][30][31][32] and 1 for inclusion in the economic component (Fig 1). 31 Studies included in the effectiveness component consisted of 1 cluster randomized controlled trial (RCT), 26 2 nonclustered RCTs, 23,24 and 1 time series analysis.…”
Section: Resultsmentioning
confidence: 99%
“…31 Studies included in the effectiveness component consisted of 1 cluster randomized controlled trial (RCT), 26 2 nonclustered RCTs, 23,24 and 1 time series analysis. 25 Studies included in the (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the early 1980s, Yokley & Glen wick (75) found that a specific letter combined with a lottery ticket incentive was more effective in the short term than a specific letter alone or combined with increased clinic hours, and all were more effective than a general mailout. However, by three months postintervention, the specific letter alone was the most cost-effective intervention, at an estimated cost of $2.27 per additional child immunized, compared with $6.91 for the specific letter plus lottery ticket, $6.28 for the specific letter and increased clinic hours, and $3.64 for the general mailout.…”
Section: Follow-up Systemsmentioning
confidence: 99%